The Impact Of Learning Habits And Social Support On The Learning Climate Of Package C At PKBM Delima Bandara Padang Pariaman Regency - Trinanda, Rani; Dwi Arini, Fitri (Universitas Negeri Padang, 2024)
ABSTRACTThe aim of this research is to investigate the impact of learning habits and social support on the learning climate of Package C learners at PKBM Delima Bandara, located in Padang Pariaman Regency. Employing a quantitative explanatory research approach, the study utilizes multiple regression analysis techniques. The population consists of all Package C students at PKBM Delima Bandara, totaling 77 individuals, with a sample size of 43 chosen through simple random sampling. The instrument is using questionnaires. The findings indicate that both learning habits and social support, both individually and collectively, have a positive and statistically significant influence on the learning climate of Package C. This suggests that improved learning habits and access to social support positively contribute to the creation of a conducive learning environment at PKBM Delima Bandara. Hence, it is recommended that learners focus on developing effective learning habits and leverage available social support networks to enhance the overall learning climate. Keywords: learning habits, social support, learning climate, package C